Misalignment of legal rules for recording marriages between religious couples in indonesia - Ratih Dwi Pangestu; Dedy Muharman (The International Journal of Politics and Sociology Research, 2023)
The inconsistency of legal regulations regarding the registration of marriages between couples of different religions in Indonesia is the subject of this research. The author uses a normative juridical research method with a statutory approach in this study. The primary legal materials used in this study are laws and regulations related to the problem under study, while secondary legal materials are in the form of journals, literature, books, papers, theses, dissertations whose contents are related to this research, dictionaries, encyclopedias, and other sources. another source. These legal documents are systematically compiled and analyzed qualitatively. According to the research results, the elucidation of Article 35 letter a. The Population Administration Law or abbreviated ADMINDUK Law as amended by Law Number 24 of 2013 concerning Amendments to Law Number 23 of 2006 concerning Population Administration, and Supreme Court Circular dated 30 January 2019, Number: 231/Pan/Hk 05/1/2019, there was disagreement in the rules for registering marriages between couples of different religions. Therefore, in order for these two regulations to be synchronized, the elucidation of Article 35 letter a of the ADMINDUK ACT needs to be changed, and there needs to be clear and firm rules for interfaith couple marriages so that there are no more parties to go to court for a decision.%MCEPASTEBIN%